Coordination variability and skill development in expert triple jumpers - Wilson, C.; Simpson, S.; van Emmerik, R. E. A.; Hamill, J. (Sports Biomechanics, 2008)
The aim of this study was to examine the influence of skill of expert triple jumpers on the coordination variability of lower extremity intra-limb couplings. In contrast to the traditional motor learning perspective, we hypothesized that as skill and thus performance increases, movement coordination variability will also increase. Three-dimensional kinematic and ground reaction force data were collected during the hop-step transition phase of the triple jump. Relative motion plots and a modified vector coding technique were used to quantify the coordination variability across the trials. The results were consistent with a U-shaped curve, representing coordination variability, as skill increases. The high coordination variability in less skilled athletes is present while the appropriate characteristics defining the movement coordination patterns are acquired. This coordination variability may not be beneficial to performance. As the refinement of these characteristics is achieved, coordination variability decreases, resulting in a more consistent or regulated performance. In the final stages of developing a skilled performance, a functional variability is accessed that brings flexibility to the system allowing it to cope with perturbations. This study highlights the need to address the learning effect when analysing coordination variability from a dynamical systems perspective.